Appearance can be deceptive: A case report on raised CA 19-9 in a patient with cholecystitis and without evidence of malignancy (Bangladesh Journal of Medical Science, 2024)
Background Cancer Antigen 19-9 (CA 19-9) is a potent marker in diagnosing carcinoma, but it can be increased in several benign conditions.Method This is a descriptive observational case report on an unusual increase of CA 19-9 in benign condition. In this study, we present a case of cholecystitis whose elevated CA 19-9 level did not reflect any malignancy rather non-malignant condition.Results A 64-year male patient with cholecystitis having significant raised level of CA 19-9 (1396 U/ml). Physician suggested potential cholangiocarcinoma by depending on initial tests, however after several imaging and biopsies it was confirmed that the case was cholecystitis. After antibiotic treatment and open cholecystectomy, CA 19-9 level was dropped to 625U/ml and 4.61 U/ml respectively.Conclusion: Physicians should remain vigilant during assessing the level of CA 19-9 and the physician should not decide the disease not only by using diagnostic report of CA 19-9, but also further tests and treatment response monitoring are essential.Bangladesh Journal of Medical Science Vol. 23 No. 03 July’24 Page : 869-872